Endoscopic tympanoplasty type I using interlay technique - Masahiro Takahashi; Masaomi Motegi; Kazuhisa Yamamoto; Yutaka Yamamoto; Hiromi Kojima (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Tympanoplasty using the interlay technique has rarely been reported in transcanal endoscopic ear surgery, unlike the underlay technique. This is because many surgeons find it challenging to detach the epithelial layer of the tympanic membrane using only one hand. However, the epithelial layer can be easily detached from the inferior part of the tympanic membrane. Another key point is to actively improve anteroinferior visibility even if the overhang is slight because most perforations and postoperative reperforations are found in the anteroinferior quadrant of the tympanic membrane. We report the application of the interlay technique in endoscopic tympanoplasty type I for tympanic perforations. Methods We retrospectively reviewed the medical records of 51 patients who had undergone tympanoplasty using the interlay technique without ossiculoplasty between 2017 and 2020. We then compared the data with those of patients who underwent microscopic surgery (MS) using the underlay technique between 1998 and 2009 (n = 104). No other technique was used in each group during this period. Repair of tympanic membrane perforation and hearing outcomes were assessed for > 1 year postoperatively. Results The perforation sites were limited to the anterior, posterior, and anterior–posterior quadrants in 23, 1, and 27 ears, respectively. Perforations were closed in 50 of the 51 ears (98.0%), and the postoperative hearing was good (average air-bone [A-B] gap was 6.8 ± 5.8 dB). The surgical success rate for the repair of tympanic membrane perforation was not significantly different from the MS group (93.3%, P = 0.15). The average postoperative average A-B gap in the group that underwent the interlay technique was significantly different from that in the MS group (10.1 ± 6.6 dB, P < 0.01). Conclusion The interlay technique should be considered as one of the treatment methods in endoscopic surgery for tympanic perforations. Further study of the postoperative outcomes of this procedure should be conducted to establish the optimal surgical procedure for tympanic perforations. Trial registration: This study was retrospectively approved by the Institutional Review Board of the Jikei University, Tokyo, Japan (approval number: 32-205 10286). Video abstract Video abstract